ANALISIS KEMAMPUAN DALAM MENYELESAIKAN PERHITUNGAN PERSEDIAAN PADA SISWA SMK NEGERI 1 PEMULUTAN - suti wahyuni; Diana Widhi Rahmawati; Hendri Gunawan (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
This study aims to evaluate how well students can understand the calculation of merchandise inventory carried out by 11th-grade Accounting and Institutional Finance (AKL) students at SMK Negeri 1 Pemulutan. The method applied in this study is descriptive quantitative. A total of 53 students from class XI AKL 2 and XI AKL 3 were involved as samples, selected using purposive sampling. Data were collected through cognitive ability tests covering understanding, application, analysis, and synthesis aspects. Data analysis was done using a descriptive statistical approach by calculating percentages. The results of the study show that overall, students' cognitive abilities in completing merchandise inventory calculations are classified as good. However, comprehension skills are still an area that needs more attention because they have the lowest percentage compared to other indicators. Therefore, there needs to be a learning strategy that focuses more on mastering the basic concepts of merchandise inventory so that students' cognitive abilities can develop more optimally.